Making Property Tax Reform Happen in China - OECD (Organization for Economic Cooperation & Development, 2022)
This report looks at crucial elements of reforms to growth-friendly recurrent taxes on immovable property. Tax design practices in place in OECD and partner countries are compared and analysed through the lenses of economic theory and empirical analysis.